Tool Enhancement For Collaborative Software Engineering Education - Utomo, Danang Wahyu (2014)
Software development can be done by people have different background in various environments. Recent researches indicate that collaborative software development is important for student. Individual expected to work together become teamwork. The teamwork expected to understand collaborative software development include methods and tools in project development. Student with lack experience and communication skill is major problem in the collaborative software development. Teamwork skills are important in collaborative software development. Discussion and assessment component is a method to develop teamwork skill. This study performed develop collaborative tool that can support collaborative work of student. Apply assessment component in the collaborative tool to assess individual and team work. In testing and evaluation phase, the result indicates that the collaborative tool can be used to support collaborative work of student and to evaluate individual and team work skill.